1997
DOI: 10.1111/j.1600-051x.1997.tb00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐concept and dental health behaviours in adolescents

Abstract: The purpose of this investigation was to examine the relation between some dental health behaviours and 2 measures of self-concept in adolescents. Data from a survey of 41142, 12-16-year-old children from 244 secondary schools throughout England were analysed to obtain information about their frequencies of toothbrushing, use of dental floss and dental attendance, and whether they recalled advice about toothbrushing, in relation to self-esteem and health locus of control (HLOC). Subjects completed a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 11 publications
7
79
0
3
Order By: Relevance
“…A more external locus of control as shown by higher SILOC scores was associated with higher dental neglect, caries, and plaque and gingivitis prevalence as well as with a tendency to postpone needed dental treatment. Previous research has shown that an external locus of control was associated with poorer oral health indicators [11,13,14] well as poorer dental attendance [17,29,30], which were in agreement with the findings of our study. These factors were considered for validation of the SILOC as they have been shown to be associated with locus of control in the past.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A more external locus of control as shown by higher SILOC scores was associated with higher dental neglect, caries, and plaque and gingivitis prevalence as well as with a tendency to postpone needed dental treatment. Previous research has shown that an external locus of control was associated with poorer oral health indicators [11,13,14] well as poorer dental attendance [17,29,30], which were in agreement with the findings of our study. These factors were considered for validation of the SILOC as they have been shown to be associated with locus of control in the past.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have shown a relationship between locus of control and oral health status, but the findings have been contradictory [11,13,14]. Similarly previous studies have shown a relationship between locus of control and oral health behaviors as well [15][16][17][18] but with equally contradictory results [19][20][21].…”
Section: Introductionmentioning
confidence: 63%
“…36 They have distinct dental needs due to a potentially high rate of caries, increased risk of TDIs, a tendency towards poor nutritional habits and the initiation of tobacco use, eating disorders as well as unique social and psychological needs. [37][38][39] Public dental health interventions to address DN may be more relevant for deprived adolescents whose dental needs are at greater risk of neglect than for adolescents across the population as a whole. Finally, as DN may overlap with other types of child neglect, resources could be more efficiently allocated.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,27 Among the various psychological inventories, the LOC scale has proved particularly useful, especially in the prediction of healthenhancing behavior. [3][4][5][6][7][8] This study was inspired by a previous report that concluded that LOC information might be useful to enhance patient compliance in orthodontic treatment. 9 Although a specific LOC questionnaire for orthodontic patients 9 is available, there were 3 reasons for selecting the RICS and the NSECS in this study: (1) the RICS and the NSEC have already been used many times in their translated forms with proven reliability and validity for the general population and orthodontic patients 15,16,[23][24][25][26] ; (2) a minimum elementary level of education is required for use; and (3) these tests are practical for use in clinical practice with free distribution and rapid completion, and most patients can complete them in 15 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…2 LOC has been studied in many subjects to enhance the understanding and prediction of human behaviors, especially those affecting health. 3 In dentistry, LOC studies have been used to enhance oral hygiene, [4][5][6] to evaluate prognosis of periodontal treatment, 7 and to investigate the relationship between LOC and craniomandibular dysfunction. 8 More specifically, a LOC scale, introduced for orthodontic patients and their parents, has been shown to be a valid and reliable tool for orthodontist-patient communication.…”
mentioning
confidence: 99%